1991
DOI: 10.3109/00365549109023380
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of cerebrospinal fluid adenosine deaminase determination

Abstract: We measured the activity of adenosine deaminase (ADA) in the cerebrospinal fluid of 3 patients with tuberculous meningitis, 38 with viral meningitis, 15 with bacterial meningitis, 5 with malignant lymphoma, 11 with cerebrovascular diseases and 13 with miscellaneous neurological disorders. The highest ADA activities were observed in patients with tuberculous meningitis (median 21.3 U/l, range 20.0-23.0) and lymphoma (13.0 U/l, range 4.0-25.0). The sensitivity of the test for diagnosing tuberculous meningitis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 14 publications
3
32
0
1
Order By: Relevance
“…Similarly CSF-CRP by latex agglutination is a useful test for bacterial meningitis with reported high sensitivity (12,13,14).The mean ADA value in our study was 12.12±3.13 IU/L for TBM group and was significantly higher (p<0.001) than the partially treated pyogenic meningitis (5.39±2.70 IU/L) and aseptic meningitis (1.92±0.56 IU/L). There has been conflicting report regarding the diagnostic value of ADA in children as compared to adults, in whom 96-100% sensitivity has been, described (5,6,17). Our study confirms the utility of ADA as diagnostic test for TBM in children.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Similarly CSF-CRP by latex agglutination is a useful test for bacterial meningitis with reported high sensitivity (12,13,14).The mean ADA value in our study was 12.12±3.13 IU/L for TBM group and was significantly higher (p<0.001) than the partially treated pyogenic meningitis (5.39±2.70 IU/L) and aseptic meningitis (1.92±0.56 IU/L). There has been conflicting report regarding the diagnostic value of ADA in children as compared to adults, in whom 96-100% sensitivity has been, described (5,6,17). Our study confirms the utility of ADA as diagnostic test for TBM in children.…”
Section: Discussionsupporting
confidence: 81%
“…ADA is an enzyme with principal biologic activity in Tlymphocytes (10). Raised levels have been used as diagnostic marker in many studies (5)(6)(7)(8)(9)11). Similarly CSF-CRP by latex agglutination is a useful test for bacterial meningitis with reported high sensitivity (12,13,14).The mean ADA value in our study was 12.12±3.13 IU/L for TBM group and was significantly higher (p<0.001) than the partially treated pyogenic meningitis (5.39±2.70 IU/L) and aseptic meningitis (1.92±0.56 IU/L).…”
Section: Discussionmentioning
confidence: 99%
“…6 Chotmongkol V et al identified a CSF ADA level of 15.5U/l as the best cut-off value to differentiate tuberculous meningitis and non-tuberculous meningitis, with a sensitivity of 75% and specificity of 93%. 7 When tuberculous meningitis was compared with aseptic and carcinomatous meningitis, a CSF ADA level of 19.0 U/l was the best cut-off value for differentiation, with a sensitivity of 69% and a specificity of 94%.…”
Section: Discussionmentioning
confidence: 99%
“…Aunque no hay un consenso con respecto al valor normal de ADA, varios estudios retrospectivos indican que una concentración mayor de 9 o 10 U/l en el LCR es muy sensible y específica para el diagnóstico de meningitis tuberculosa o de neurobrucelosis 1 . Además de las etiologías mencionadas, la ADA puede estar elevada en la meningitis sarcoidea 2 , la infiltración meníngea por leucemia o linfoma 3 , la toxoplasmosis cerebral, el infarto cerebral 3 , la meningitis criptocócica, la neurosífilis y otras meningitis asépticas 4 . Recientemente se ha descrito un caso de meningitis por Listeria con ADA elevada (12,3 U/l) 5 .…”
Section: Sr Directorunclassified